2021
DOI: 10.1155/2021/6679787
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Improves Yield Performance by Enhancement in Physiological Responses, Crop Imagery, and Leaf and Culm Sheath Morphology in New Rice Line, PadiU Putra

Abstract: The PadiU Putra rice line is a blast-resistant and high-yield rice line with high potential. The application of topdressing and the foliar applied method of silicon (Si) treatments could strengthen the culm to resist breakage and ultimately increase yield production. Treatments which consisted of a control, a Si topdressing, and a Si foliar applied were arranged in a randomised complete block design. At 55 days after transplanting (DAT), the foliar applied Si treatments had 59% higher dry matter partitioning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…The improvement of rice crops by application of Si fertilizer was due to the increase in the yield characteristics of rice, as found in the present study where the numbers of tillers and panicles per plant and percentage of filled grains were increased under higher Si application [ 19 ]. Several studies have demonstrated that a high rate of Si fertilizer could promote the strength of stems, increase chlorophyll content and photosynthetic activity, and consequently improve productivity in rice crops [ 7 , 8 , 10 ]. The increase in rice grain yield by Si is also associated with an improvement in some morphological and physiological characteristics of the reproductive system, including pollen vigor, strength and thickness of the anther wall, and pollen germination rate [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of rice crops by application of Si fertilizer was due to the increase in the yield characteristics of rice, as found in the present study where the numbers of tillers and panicles per plant and percentage of filled grains were increased under higher Si application [ 19 ]. Several studies have demonstrated that a high rate of Si fertilizer could promote the strength of stems, increase chlorophyll content and photosynthetic activity, and consequently improve productivity in rice crops [ 7 , 8 , 10 ]. The increase in rice grain yield by Si is also associated with an improvement in some morphological and physiological characteristics of the reproductive system, including pollen vigor, strength and thickness of the anther wall, and pollen germination rate [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, grain yield increases by Si application have been found to be associated with Si concentration in the shoot and grain [ 9 ]. A high concentration of Si in plant tissues has been demonstrated to play a major role in the growth and productivity of rice through increases in the strength of stems, the erectness of leaves, and the photosynthetic rate [ 10 ]. The wide variation of Si concentration in plants depends on the potential of uptake and transport mechanisms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of Si on plant growth, productivity, photosynthesis, balanced nutrient availability, and the mechanisms for reactive oxygen species scavenging have been demonstrated in numerous studies [17,18]. Thus, the application of Si has been widely implemented on various crops to alleviate the deleterious effects of water, salt, and heavy-metal stresses, as well as protect against pest infestation and disease [1,7,[9][10][11][18][19][20][21]. Si has been reported to promote stem strength by increasing lignin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Si has been reported to promote stem strength by increasing lignin accumulation. In rice, stem strengthening helps to reduce lodging, thus preventing mutual shading, maintaining canopy photosynthesis, and consequently improving productivity [20,22]. Ahmad and Haddad [19] demonstrated that Si application positively influenced the antioxidant system in Triticum aestivum plants.…”
Section: Introductionmentioning
confidence: 99%
“…They counted manually the actual weeds to check the real weeds in the field. Berahim et al, [124] also collected the ground and agronomic data and related with the aerial imagery. They found that physiological responses similar to the aerial imagery in rice field monitoring.…”
Section: Discussionmentioning
confidence: 99%